139 GOSH – a cultural space. (December 2018) - Hall, S; Reiss, V; Moore, C; Copsey, H
Abstract : A hospital is obviously a clinical place. But it can also be a cultural space. A community of potential audiences and artists. Patients, families and staff are not only consumers but also creators, of culture. This is an exciting time for arts in hospitals and arts in health generally. The recent publication of the report by the All Party Parliamentary Group on Arts, Health and Wellbeing (APPGAHW), 'Creative Health: The Arts for Health and Wellbeing', shone a spotlight on the multitude of positive benefits, impacts and effects of creativity in healthcare settings. This presentation will give an overview of the GOSH Arts programme and the evidence base for arts in hospitals. Why bother having an art team and what is the impact? GOSH Arts is the arts programme at Great Ormond Street Hospital. Our wide-ranging work is designed to encourage creativity and improve the hospital environment of everyone. We deliver workshops, performances, exhibitions and art commissions that inspire creativity, create welcoming environments, and offer meaningful cultural opportunities for patients, families and staff.